2021
DOI: 10.1186/s12933-021-01300-y
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of cardiovascular outcome trial effects to the real-world population of patients with type 2 diabetes

Abstract: Background Transferring results obtained in cardiovascular outcome trials (CVOTs) to the real-world setting is challenging. We herein transposed CVOT results to the population of patients with type 2 diabetes (T2D) seen in routine clinical practice and who may receive the medications tested in CVOTs. Methods We implemented the post-stratification approach based on aggregate data of CVOTs and individual data of a target population of diabetic outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[18][19][20][21][22][23] Additional potential benefits of empagliflozin and other SGLT2 inhibitors include improved cardiovascular energetics, reduced vascular tone and blood pressure, decreased renal dysfunction, increased circulating levels of ketone bodies, protection against pulmonary ischemia/reperfusion injury, and overall reduced systemic inflammation. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] On these grounds, we investigated the effects of empagliflozin on frailty in diabetic and hypertensive older adults. To mechanistically confirm our results, we evaluated the effects of empagliflozin on mitochondrial oxidative stress and permeabilization in human endothelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23] Additional potential benefits of empagliflozin and other SGLT2 inhibitors include improved cardiovascular energetics, reduced vascular tone and blood pressure, decreased renal dysfunction, increased circulating levels of ketone bodies, protection against pulmonary ischemia/reperfusion injury, and overall reduced systemic inflammation. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] On these grounds, we investigated the effects of empagliflozin on frailty in diabetic and hypertensive older adults. To mechanistically confirm our results, we evaluated the effects of empagliflozin on mitochondrial oxidative stress and permeabilization in human endothelial cells.…”
mentioning
confidence: 99%
“…18–23 Additional potential benefits of empagliflozin and other SGLT2 inhibitors include improved cardiovascular energetics, reduced vascular tone and blood pressure, decreased renal dysfunction, increased circulating levels of ketone bodies, protection against pulmonary ischemia/reperfusion injury, and overall reduced systemic inflammation. 24–37…”
mentioning
confidence: 99%
“…Of note, using the same real-world dataset, there was high heterogeneity between the proportion of patients that could have been included in different trials, emphasizing the problem of generalizability. However, a recent study evaluated the transposition of cardiovascular outcome trial effects to the real-world population using CVOT stratum-specific effects, showing that the cardiovascular benefits are transferable to a much different real-world population [ 49 ].…”
Section: Summary and Discussion Of The Glp-1 Ra Cvots Resultsmentioning
confidence: 99%
“…Our study determined the causal relationship between glycemic control patterns and atherosclerosis progression; however, we could not give more suggestion about the effects of the new treatments for diabetes. The recent study revealed a decreased risk of coronary heart disease in patients with type 2 diabetes treated with GLP-1 receptor agonists and SGLT2 inhibitors, which provided the idea for our next research [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%